Memahami Hubungan Agama Dan Masyarakat, Iman Dalam Pengaruh Media Sosial - Yersi Hotmauli Berutu (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Society in the historical strata has had a fairly close relationship with religion since prehistoric times. For society, religion is seen as the beliefs and behaviors that society uses to address important problems that cannot be solved by the technical systems and organizational techniques for which it is known. To overcome this limitation, humans use the manipulation of supernatural powers. The notion of "culture" is generally understood as a complex definition. Culture or culture can be thought of as a concept whose definition follows the content of its users, although it also refers to objective reality. That is, one person may have an opinion about "culture" or "culture", but another person may object to the words used; Because it requires the person concerned to appreciate his culture. Like the definition of "culture" above, "religion" also has different meanings, both from the point of view of its adherents and from the point of view of the sciences that study it (Sena Adiningrat, 2010). In all areas of world society; religion, culture and belief are three important and very basic elements. All three have a very strong bond and correlation as the core of society, so that even in the craziest and sane times, they are never broken. Because where there is an association or community or society, there is a habitus, then lived and continues to exist, then it becomes a culture. Meanwhile, religion is a belief in one's conscience, which essentially has an inner connection with feelings and the desire to embrace something and believe in it. So religion requires faith or belief. So believing in something important in religion is called faith.